2003
DOI: 10.1203/01.pdr.0000069846.64389.dc
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Restriction, Preeclampsia, and Intrauterine Mortality at High Altitude in Bolivia

Abstract: Infant mortality and stillbirth rates in Bolivia are high and birth weights are low compared with other South American countries. Most Bolivians live at altitudes of 2500 m or higher. We sought to determine the impact of high altitude on the frequency of preeclampsia, gestational hypertension, and other pregnancy-related complications in Bolivia. We then asked whether increased preeclampsia and gestational hypertension at high altitude contributed to low birth weight and increased stillbirths. We performed a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
221
2
12

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 251 publications
(249 citation statements)
references
References 17 publications
14
221
2
12
Order By: Relevance
“…Uterine artery Doppler flow parameters have been used to assess the risk of developing preeclampsia and fetal growth restriction (16)(17)(18). The incidence of pregnancy-related complications such as preeclampsia and eclampsia was found to be higher in women living at a high altitude than that in women living at a low altitude (7,8). We observed lower PI and RI indices in both the right and left uterine arteries at the moderately high altitude than those at the sea level.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Uterine artery Doppler flow parameters have been used to assess the risk of developing preeclampsia and fetal growth restriction (16)(17)(18). The incidence of pregnancy-related complications such as preeclampsia and eclampsia was found to be higher in women living at a high altitude than that in women living at a low altitude (7,8). We observed lower PI and RI indices in both the right and left uterine arteries at the moderately high altitude than those at the sea level.…”
Section: Discussionmentioning
confidence: 50%
“…A recent study (21) revealed the presence of endoplasmic reticulum stress, protein synthesis inhibition, and slowed proliferation in the placenta in response to chronic hypobaric hypoxia. On the other hand, Keyes et al (23) reported that both high altitude and hypertensive complications are independently associated with the reduction in the birth weight. In another study (24), a significant increase in the reactive oxygen species production in uterine arteries and pressure-dependent uterine arterial myogenic tone was found in pregnant sheep exposed to highaltitude (3801 m) hypoxia for 110 days compared with the sea level (300 m).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of the different rates at both altitudinal zones is progressive and consistent with what is occurring in the rest of Argentina; however, rates remain persistently higher in the highlands, especially PNMR. Several studies have pointed out the increase in NMR along with altitude in different populations worldwide, [13][14][15]19 but there are practically no data on how PNMR relates to altitude.…”
Section: Discussionmentioning
confidence: 99%
“…Depending upon the early or late onset, disease can show mild or severe symptoms. Deranged liver function, thrombocytopenia and HELLP syndrome can evolve in eclampsia in severe cases [16, 17]. …”
Section: Risk Factors and Pathogenesis Of Preeclampsiamentioning
confidence: 99%